Growth and maintenance costs of leaves and roots in two populations of Quercus ilex native to distinct substrates - Laureano, Raquel G.; García-Nogales, Ana; Seco, José I.; Rodríguez, Jesús G. P.; Linares, Juan C.; Martínez, Feliciano; Merino, José (Plant and Soil, 2012)
Aims This work tests the hypothesis that growth and maintenance costs of plant organs are higher in more stressful soils. Methods Two populations of Quercus ilex L were selected in the southern Iberian Peninsula, these growing in similar climates but different soil types, namely a brown well-developed soil on slate rock, and a stressful lithosol on gypsum rock. In both localities, growth and maintenance respiration were measured in undetached young and mature leaves (trees under natural conditions) and fine roots (hydroponically grown seedling). Results Young leaves of the two populations displayed an almost identical growth cost (1.53 g glucose g -1 ). The maintenance cost was higher in the young (40.2 vs. 25.3 mg glucose g -1 day -1 ; P<0.05) and in the mature (7.64 vs. 4.33 mg glucose g -1 day -1 ; P<0.001) leaves of individuals growing in gypsum soils. The growth cost of fine roots was the same in both populations (1.18 g glucose g -1 ) while the maintenance cost was higher in the Gypsum population (8.95 vs. 7.39 mg glucose g -1 day -1 ; P<0.01). Conclusions The results show for first time that the cost of organ maintenance may be related to the degree of soil stress in their native habitats.
Keywords: ecotypes; evergreen leaves; growth respiration; maintenance respiration; mediterranean species; root respiration; sclerophylly; soil stress